Carboplatin plus nab‐paclitaxel for recurrent small cell lung cancer: A phase II study. Issue 9 (22nd March 2022) - Ikeda, Naoya; Arai, Ryo; Soda, Sayo; Inoue, Takashi; Uchida, Nobuhiko; Nakamura, Yusuke; Masawa, Meitetsu; Kushima, Yoshitomo; Okutomi, Hiroaki; Takemasa, Akihiro; Shimizu, Yasuo; Niho, Seiji
Abstract: Background: We conducted a phase II study of carboplatin plus nab‐paclitaxel for the treatment of small cell lung cancer (SCLC) after the failure of a prior standard chemotherapy containing platinum, etoposide, irinotecan, and amrubicin if indicated. Patients with interstitial pneumonia complications were included in the study. Methods: Patients received 100 mg/m 2 of nab‐paclitaxel weekly (on days 1, 8, and 15) and an AUC 5 of carboplatin on day 1. The study treatment was repeated every 3 weeks until disease progression or the appearance of unacceptable toxicities. The primary endpoint was the objective response rate. Results: A total of 21 patients were enrolled, all of whom were eligible for inclusion in the analysis. Twelve patients had pre‐existing interstitial pneumonia. The overall response rate was 19.0% (90% confidence interval [CI]: 6.8%–38.4%). The lower limit of the 90% CI for the response rate did not exceed the prespecified threshold value of 10%. Among the 12 patients with pre‐existing interstitial pneumonia, the response rate was 25%. The median progression‐free survival time was 2.5 months (95% CI: 1.5–3.4 months), and the median survival time was 5.1 months (95% CI: 2.1–8.1 months). Two patients developed interstitial lung disease; both of these patients had pre‐existing interstitial pneumonia. One of the patients died from interstitial lung disease. Conclusion: Combination chemotherapy with carboplatin plus nab‐paclitaxel for recurrent SCLC had a modest activity, although the primary study endpoint was not met. Further investigation of this regimen for patients with recurrent SCLC and interstitial pneumonia is warranted. Abstract : We conducted a phase II study of carboplatin plus nab‐paclitaxel for the treatment of small cell lung cancer after the failure of a prior standard chemotherapy containing platinum, etoposide, irinotecan, and amrubicin if indicated. Patients with interstitial pneumonia complications were permitted. Combination chemotherapy with carboplatin plus nab‐paclitaxel for recurrent small cell lung cancer had a modest activity with manageable toxicities, although the primary study endpoint was not met.